Laminar, transitional, and turbulent heat transfer measurements on a yawed blunt conical nosetip - Widhopf, George F.; United States.; Space and Missile Systems Organization (U.S.); Aerospace Corporation (Space and Missile Systems Organization, Los Angeles Air Force Station, Air Force Systems Command, United States Air Force, 1972)
Laminar, transitional, and turbulent heat-transfer rates measured on a blunt (nose radius = 2.5 in.) 9-deg half-angle cone in a M freestream conditions = 5 air flow at various angles of attack are presented. Measurements were made at nominal freestream Reynolds numbers of 48.5, 19, 11, and 4.6 time 10 to the 6th power per foot at nominal angles of attack alpha = 0, 5, 10, 15, 20, and 27 degrees. The wall-to-stagnation temperature ratio varied between 0.20 and 0.29. Detailed circumferential and axial distributions of both the heat transfer rate and surface pressure were obtained over the entire model at each test condition and angle of attack. (Author).
"72 SEP 01."
Includes bibliographic references (pages 83-85).
Laminar, transitional, and turbulent heat-transfer rates measured on a blunt (nose radius = 2.5 in.) 9-deg half-angle cone in a M freestream conditions = 5 air flow at various angles of attack are presented. Measurements were made at nominal freestream Reynolds numbers of 48.5, 19, 11, and 4.6 time 10 to the 6th power per foot at nominal angles of attack alpha = 0, 5, 10, 15, 20, and 27 degrees. The wall-to-stagnation temperature ratio varied between 0.20 and 0.29. Detailed circumferential and axial distributions of both the heat transfer rate and surface pressure were obtained over the entire model at each test condition and angle of attack. (Author).
Report prepared by The Aerospace Corporation, Technology Division, El Segundo, California, under contract No.F04701-71-C-0172
Keywords: Heat / Transmission.; Turbulence.; Laminar flow.; Aerodynamics.; Aerothermodynamics.; Aerodynamic heating.